Circulating levels of vascular endothelial growth factor in patients with Alzheimer's disease: A case-control study - Silva, Thays Martins Vital da [UNESP]; Stein, Angelica Miki [UNESP]; Coelho, Flávia Gomes de Melo [UNESP]; Rueda, Andre Veloso; Camarini, Rosana; Galduróz, Ruth Ferreira [UNESP] (Elsevier, 2023)
Background: Vascular endothelial growth factor (VEGF) and platelets seem to reflect the Alzheimer's disease (AD) associated either with vascular impairment or disease. This study aimed to compare the circulating levels of VEGF and platelets between AD patients and healthy older adults. Methods: Seventy-two older adults, divided in 40 older adults (Clinical Dementia Rating Scale – CDR = 0); and 32 Alzheimer's disease patients (clinically diagnosed – CRD = 1) participated in the present study. The groups were paired by sex, age, comorbidities and educational level. The primary outcomes included circulating plasma VEGF and platelet levels obtained by blood collection. Results: The VEGF levels were significantly different between the groups (p = 0.03), with having a large effect size ( η2 =18.15), in which the AD patients presented lower levels compared to healthy older adults. For platelets, the comparison showed a tendency to difference (p = 0.06), with a large effect size (η2 =12.95) between the groups. Conclusion: The VEGF levels and the platelet numbers were reduced in AD patients, suggesting that angiogenic factors could be modified due to AD.
Keywords: Aging; Biomarker; Dementia